Towards Climate Neutrality – The key role of the Digital Twin in Industry 5.0 - Anna Osello; Matteo Del Giudice; Angelo Juliano Donato; Andrea Fratto (Agathón)
Climate neutrality is a global challenge that requires a revolution in production models and energy use. The industrial sector, one of the leading emitters of pollutants, needs technological innovation to reverse this trend, promoting solutions to improve production, reduce energy consumption and cut operating costs. The Digital Transition to Industry 5.0 explores the complexity of the energy transition and the development of a digital twin to address the challenges of climate change. The research describes an innovative process based on Information Technologies and BIMtoBEM methodologies to develop a digital twin of the factory to implement visualisation systems, such as digital dashboards and extended reality technologies, placing human beings at the centre of the proposed methodological flow.